Czechoslovakia. Significant productivity gains with relatively small capital investment - Jiří Sláma (Osteuropa-Institut München, 1991)
The improvements in crucial parameters of operating performance could be achieved with relatively small investments. This will be achieved using concrete examples at the levels of individual businesses, which are intended to demonstrate to public authorities as well as to enterprises and their management that the necessary structural reorganization does not always involve large-scale, expensive measures. Above all, the illustrations reveal that reorganization must begin at the bottom, i.e., at the enterprise level. This study is based on extensive empirical material obtained from numerous businesses, of which only a small percentage is represented here.
Additional information: This study was prepared for the World Bank
Keywords: O52; D22; 330; Czechoslovakia; investment; productivity; transformation